Theoretical Analysis of Microeconomic Effect of Public Investment - Dada, Matthew Abiodun (Asian Journal of Economic Modelling, 2015)
We raise important questions about the relative contribution of public investment to economic development evaluated at individual household and firm level. By assuming perfect complementarity between private and public investment, we analyze how public investment influences household demand and firm profits. We equally raise an important issue on implication of different sources of funding public investment such as raising investment fund through tax revenue or borrowing from banks or through seigniorage. The study describes the desirability or otherwise of increasing the proportion of public capital in the production function and the impact of such increased capital on utility maximizing behaviour in the household sector as well as profit maximizing behaviour in the business sector.